SEARCH FOR VARIABLE STARS AND THEIR STUDY - Kokumbaeva, R. I.; Zakhozhay, V. A.; Khruslov, A. V. (Одеські астрономічні публікації, 2016)
We search for variable stars and study them using our CCD observations, observations available in the CSS, NSVS, ASAS-3 and Super-WASP online public archives.Our CCD observations were performed using the Zeiss- 1000 telescope of the V.G. Fesenkov Astrophysical Institute’s Tien-Shan Astronomical Observatory. Earlier, as a result of our search using CCD images, we detected 27 new variable stars; using the NSVS and SuperWASP databases, we detected 12 new red semiregular and irregular variable stars.In this paper, we present our study of seven known variables based on the ASAS-3 and SuperWASP databases. All these stars remained poorly studied, their light elements were unknown, variability types were considered preliminary only. We studied two eclipsing variables (FY And and V2250 Sgr) and five Mira-stars (BZ Sco, CZ Sco, FK Sco, V880 Sco and V1818 Sgr).